JIPP RESILIENSI MEMPERTAHANKAN HAFALAN AL-QURAN PADA REMAJA ALUMNI SANTRI DARUL QURAN MULIA (DQM) DITINJAU DARI RELIGIUSITAS DAN PRESTASI HAFALAN AL-QURAN SAAT PANDEMI COVID 19 - Nabilah, Nida (Psikologi UHAMKA, 2022)
Resilience in maintaining the memorization of the Koran during the Covid 19 pandemic among young DQM alumni alumni in terms of religiosity and achievement in memorizing the Koran is the goal of this research. Memorizing the Al-Qur'an for DQM (Darul Qur'an Mulia) students while in Islamic boarding schools get many convenience facilities. Problems occur when they become alumni. There are no special room facilities and friends who memorize the Al-Qur'an together, there are no ustad/ustadzah who guide or help during murojaah. Especially during the Covid 19 pandemic. There was a closure of tahfidz institutions. On the other hand, alumni of DQM students have a lot of activities such as working or studying. Resilience in a lot of literature is the key to success during the covid 19 pandemic. Factors that are suspected of strengthening the resilience of DQM alumni students include Religiosity and achievement in the number of memorization of the Qur'an by DQM alumni students. The participants were 130 youth alumni of DQM alumni (age 17-25 years). Participants were obtained by accidental sampling. Resilience was measured using the CD-RISC measuring instrument from Connor and Davidson. Religiosity is measured using the Centrality of Religiousity Scale (CSR) from Huber, S and Huber, W.O. Meanwhile, the achievement of memorizing the Al-Qur'an was obtained from the large number of DQM students' alumni memorizing. The analysis technique uses multiple regression. The results found that there was (1) a fairly strong correlation of the three variables of religiosity, achievement in memorizing the Koran with resilience with a value of R = 0.547. And R2 = 29.9. with a significant value of religiosity for resilience of P <0.05 with a Beta of = 81.7. (2) whereas the achievement of memorizing the Qur'an for resilience has a P value > 0.05. with Beta = 22.7. The conclusion is that there is a significant effect of religiosity and achievement on memorizing the Koran on the resilience of young DQM alumni alumni during the Covid 19 pandemic. Resilience is more influenced by religiosity than achievement by memorizing the number of Al-Qur'an